Identification of divergent isolates of Banana Mild Mosaic Virus and development of a new diagnostic primer to improve detection - Hanafi, Marwa; Tahzima, Rachid; Ben Kaab, Sofiene; Tamisier, Lucie; Roux, Nicolas Stephan M.; Massart, Sébastien (MDPI, 2020)
This study aims to describe the identification and genome sequencing of two isolates of Banana Mild Mosaic Virus, and, based on the virus sequences available in GenBank, to design and test a new diagnostic primer for a routine indexing use.